Clinical analysis of first branchial cleft anomalies in children. Issue 3 (17th October 2018) - Liu, Wei; Liu, Bing; Chen, Min; Hao, Jinsheng; Yang, Yang; Zhang, Jie
Abstract: Importance: First branchial cleft anomaly (FBCA) is a rare disease that is difficult to diagnose and is associated with a high rate of complications. However, the difference between two types of FBCA and how to avoid complications are not clear enough. Objective: We retrospectively analyzed type I and II (Work's classification) FBCAs in children to demonstrate the difference between the two types of FBCAs, especially with respect to understanding the relationship between FBCAs and the facial nerve Methods: We retrospectively reviewed patients with FBCAs who were treated in Beijing Children's Hospital from 2013 to 2017. The patients' clinical data, relationship of the FBCA with the facial nerve, and postoperative complications were recorded. Results: The study included 70 patients with FBCAs. In total, 41 (58.6%) patients had a type I FBCA, and 29 (41.1%) had a type II FBCA. A cystic mass was present in 34 (48.6%) patients. Sixty‐two (88.6%) patients had a history of incision and drainage and nine (12.8%) had a history of excision surgery in other hospitals. The accuracy rate of magnetic resonance imaging was higher than ultrasound and much higher than computed tomography. Thirty‐eight (92.7%) type I FBCAs had no close relationship with the facial nerve. The facial nerve in 14 (48.3%) patients with type II FBCAs was located superficial to and above the mass. Fifteen (51.7%) type II facial nerves were located on the deep side of the mass. All patients in the study had an abnormal external auditory canal (EAC). Three patients had temporary facial palsy that resolved within one week. Eleven patients with type I FBCAs had mild EAC stenosis. No recurrence was observed. Interpretation: Type II FBCAs had a close relationship with the facial nerve, especially when the lesion was located in the mandible angle. All patients with FBCAs had an EAC abnormality. The abnormal skin and cartilage of the EAC should be excised together to avoid recurrence.